Lithography-free fabrication of field effect transistor channels with randomly contact-printed black phosphorus flakes - Yoo, Seolhee; Kim, Sangsig; Song, Yong-Won (ELSEVIER SCI LTD, 2018)
Black phosphorus (BP) has distinctive properties of tunable direct band gap as a semiconductor material, and both high carrier mobility and on/off switching performance for electronic devices, but has a significant drawback of material degradation in ambient atmosphere. Also, unlike graphene or MoS2 , BP is only synthesized in bulk shapes limiting the fabrication of thin film-based devices. We demonstrated a contact printing process for BP field effect transistors (FET) with the steps of mechanical exfoliation of BP flakes and their randomized stamping in dry-transfer regime. The contact printing featured by fast, continuous and solvent-free process on the pre-patterned electrodes guarantees high process efficiency providing immunity against the chemical degradation of BP layers. With asymmetric I-V characteristics, the resultant BP-channelized FET shows the electrical properties of on/off current ratio, hole mobility, and subthreshold swing as > 10(2) , similar to 130 cm(2)/Vs, and similar to 4.6 V/dec, respectively.
Keywords: PHOTORESPONSE